Pemberdayaan Masyarakat Melalui Pengelolaan Sampah - Yuliana, Silvia Dwi; Sarbini, Ahmad (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
The never-ending waste problem has forced several parties to try to reduce the amount of waste that is disposed of in landfills, one of which is to create a waste bank and seek to manage waste wisely for the community. The purpose of this research is to find out the efforts, processes and results of waste management that have an impact on community empowerment. This research is a descriptive qualitative research where the data is obtained based on direct observation. Based on the results of this study, it shows the efforts made by waste banks to increase community participation, by conducting socialization, coaching, picking up waste that will be saved to customers' places. The waste management process is carried out by raising awareness, strengthening, and providing relevant programs and monitoring and evaluation will be carried out later. The results of waste management can improve the welfare of the people who save waste in the main garbage bank in Bandung City and the results can be seen from the large volume of waste that is reduced to TPA and the nominal money issued by the waste bank to buy waste from the community.